2020
DOI: 10.1016/j.omtn.2020.08.003
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: lncRNA lnc-TSI Inhibits Metastasis of Clear Cell Renal Cell Carcinoma by Suppressing TGF-β-Induced Epithelial-Mesenchymal Transition

Abstract: The transforming growth factor-β (TGF-β)/Smads signal plays an important role in cancer metastasis by mediating the epithelial-mesenchymal transition (EMT) in cancer cells. lnc-TSI is a recently identified long noncoding RNA that negatively regulates the TGF-β/Smads signal. The present study was conducted to test the hypothesis that lnc-TSI inhibits metastasis in clear cell renal cell carcinoma (ccRCC) by regulating the TGF-β/Smad3 pathway. Herein, we show that lnc-TSI was upregulated in ccRCC cells and tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Notably, the effect of lncRNA on the epithelial-mesenchymal transition (EMT) of tumor cells has also been confirmed in recent studies [ 15 , 16 ]. EMT is an essential step in the metastasis of malignant tumors, which can transform epithelial-like cells into a mesenchymal-like cell state.…”
Section: Introductionmentioning
confidence: 80%
“…Notably, the effect of lncRNA on the epithelial-mesenchymal transition (EMT) of tumor cells has also been confirmed in recent studies [ 15 , 16 ]. EMT is an essential step in the metastasis of malignant tumors, which can transform epithelial-like cells into a mesenchymal-like cell state.…”
Section: Introductionmentioning
confidence: 80%
“…Lnc-TSI impedes the phosphorylation of SMAD3 by blocking the interaction between SMAD3 and TGFBR1 at the MH2 domain. Consequently, the TGF-β/SMADs signaling pathway is inhibited, which suppresses epithelial–mesenchymal transition [ 78 ]. LncRNAs can also regulate the TGF-β signaling pathway by modulating its co-factors.…”
Section: The Transforming Growth Factor (Tgf)-β Signaling Pathwaymentioning
confidence: 99%
“…lnc-TSI reduced invasive and metastasizing potential of ccRCC cells [ 23 ]. Mechanistically, it was shown that lnc-TSI interacted with the MH2 domain of SMAD3 and blocked the association between TGFβ receptor I and SMAD3 in ccRCC cells.…”
Section: Lnc-tsimentioning
confidence: 99%
“…Mechanistically, it was shown that lnc-TSI interacted with the MH2 domain of SMAD3 and blocked the association between TGFβ receptor I and SMAD3 in ccRCC cells. Metastatic lesions were considerably enhanced in mice inoculated with lnc-TSI-silenced Caki-1 cells, whereas lnc-TSI overexpression markedly reduced the metastatic lesions in tumor bearing mice [ 23 ].…”
Section: Lnc-tsimentioning
confidence: 99%